Utilization of Intraparotid Segments of Superficial Temporal Vessels for Head and Scalp Free Flap Microanastomosis: A Clinical, Histological, and Cadaveric Study - Venkatesh, Vishnu; Fracol, Megan; Turin, Sergey; Ellis, Marco; Alghoul, Mohammed (Journal of Reconstructive Microsurgery, 2020)
Background The superficial temporal vessels (STV) are an underutilized target for head and neck microvascular reconstruction. Most surgeons regard the dissection as difficult, unreliable, and the anastomosis prone to vasospasm. The intraparotid course of the STV may provide more reliable flow without accompanying morbidity.Methods A retrospective review of patients who underwent head and scalp free flap reconstruction utilizing STV intraparotid segment was performed. Demographic factors such as intraoperative and postoperative complications are reported. Five bilateral cadaver heads were dissected to describe the relationship to the facial nerve. STV histology was performed on four of the cadavers, noting intraluminal diameter and vessel wall thickness.Results Thirty-nine patients underwent free flap reconstruction with anastomosis to intraparotid STVs. Defect etiology included tumor resection (71.8%), traumatic brain injury (10.3%), intracranial bleed (12.8%), and acute trauma (5.1%). Flaps transferred included anterolateral thigh (51.3%), latissimus (33.3%), thoracodorsal artery perforator (7.7%), radial forearm (2.8%), and vastus lateralis (5.1%). Two flaps (5.1%) required takeback for arterial thrombosis, with one incidence of total flap loss (2.8%). There were no instances of transient or permanent facial nerve damage nor sialocele. On cadaver dissection, three distinct vessel segments were identified. Segments 1 and 2 represented the STVs superior to the upper tragal border. Segment 3 (intraparotid segment) began at the upper tragal border and STVs enlarged with a targeted anastomosis point at an average of 16.3 mm medial and 4.5 mm inferior to the upper border of the tragus. The frontal branch coursed 11.7 mm inferior and 11.5 mm anterior to this point. On histology, the intraluminal diameter of segment 3 was significantly larger than segment 2 (1.2 vs. 0.9 mm, p = 0.007).Conclusion Head and neck free flap reconstruction with microanastomosis to the intraparotid segment of STVs can be safely and reliably performed.
Keywords: head and neck reconstruction; superficial temporal artery; superficial temporal vessels